Bio-enrichment of phenolics and antioxidant activity of combination of Oryza sativa and Lablab purpureus fermented with GRAS filamentous fungi; Resource-Efficient Technologies; Vol. 3, iss. 3 - Pardeep Kumar Sadh; Pooja Saharan; Surekha Duhan; Joginder Singh Duhan (2017, 2017)
Title screen